2013
DOI: 10.3791/50096
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Left Ventricular Wall Stress and Improvement in Function in Failing Hearts using Algisyl-LVR

Abstract: Injection of Algisyl-LVR, a treatment under clinical development, is intended to treat patients with dilated cardiomyopathy. This treatment was recently used for the first time in patients who had symptomatic heart failure. In all patients, cardiac function of the left ventricle (LV) improved significantly, as manifested by consistent reduction of the LV volume and wall stress. Here we describe this novel treatment procedure and the methods used to quantify its effects on LV wall stress and function.Algisyl-LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Regional myofiber stress was computed using a validated mathematical model, as described elsewhere in detail [26] and shown in a video [27], except for the following differences. First, the in-vivo LV geometries of the mathematical (finite element) models were based on echocardiography (the .stl-files described above) instead of MRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional myofiber stress was computed using a validated mathematical model, as described elsewhere in detail [26] and shown in a video [27], except for the following differences. First, the in-vivo LV geometries of the mathematical (finite element) models were based on echocardiography (the .stl-files described above) instead of MRI.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in large [1618] and small [1921] animals, clinical evaluations in humans [2224], as well as computational models [2527] have all suggested that injection of biomaterials can limit LV remodeling post MI and improve LV function. Unlike other surgical approaches that modify the size of the dilated ventricle, myocardial injection with biopolymers decreases wall stress and improves regional and global LV function [28].…”
Section: Introductionmentioning
confidence: 99%
“…The separate material components are mixed immediately before use and then combined in one syringe for delivery as direct intramyocardial injections (Lee et al, 2013b). The polymer forms solid inclusions inside the myocardial wall and achieves its final material stiffness of 3–5 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, the results from the phase I/II clinical trial pilot study for the treatment were published (NCT00847964). (26) In the trial, three patients who were also undergoing revascularisation were treated. The trial was unblinded, non-randomised and had no control.…”
Section: Acellular Materials Based Scaffoldsmentioning
confidence: 99%